Evaluation of Flow Diverter Stent Performance for Effective Cerebral Aneurysm Treatment - 전여진 (The Graduate School, Ajou University, 2024)
Flow diverter (FD) represents a promising approach for managing wide necked intracranial aneurysms through modulation of hemodynamics within the aneurysm sac. Nonetheless, challenges persist in the procedural technique, often resulting in suboptimal deployment or placement. This investigation focuses on three variants of FDs with alterations in wire composition while maintaining identical structural design. Variations in physical characteristics such as pre- and post-deployment stent dimensions, radial force, and radiopacity were assessed. Utilizing a simulated model, the deployment performance and trackability force of these FDs were scrutinized. Additionally, the deployment behavior within a 3D printed aneurysm model was analyzed. The NiTi FD, comprising solely of nitinol (NiTi) wire, exhibited complete size recovery and 42% to 45% metal coverage post-loading, with low trackability force (10.9 to 22.9gf), facilitating smooth maneuverability within the delivery system. However, its limited X-ray visibility renders it unsuitable for clinical use. The NiTi-Pt/W FD, incorporating a blend of NiTi and Platinum/Tungsten (Pt/W) wires, demonstrated superior radiopacity and compression force (6.03±0.29 gf) but encountered elevated trackability force (22.4 to 39.9gf) and susceptibility to mesh loosening, complicating the procedure. The NiTi(Pt) FD, utilizing platinum-core nitinol (NiTi(Pt)) wire, exhibited comparable trackability force (11.3 to 22.1gf) to NiTi FD with uniform deployment, enhancing procedural ease, albeit with concerns regarding expansion force (1.79±0.30 gf) and potential migration. Since FDs are implanted in blood vessels, hemocompatibility is a critical performance characteristic. This study also explores hemocompatibility improvements through Phosphorylcholine (PC) coating, which is commercially accessible and easy to use. SEM/EDX analysis confirmed the PC coating on the FD specimen. The PC coated FD demonstrated improved antifouling effects in the flow test and enhanced hemocompatibility in both platelet adhesion and blood flow tests. This comparative analysis sheds light on how diverse wire materials impact FD performance, providing insights for clinicians and researchers to optimize FD selection and design for effective intracranial aneurysm treatment. Though preliminary, this study lays groundwork for future investigations in this domain. Keywords: flow diverter; nitinol; platinum core nitinol; stent; aneurysm treatment; trackability force; simulated model, phosphorylcholine, hemocompatibility, antifouling effect, platelet adhesion
학위논문(박사)--의용공학과,2024. 8
Keywords: flow diverter